The Politics of Fishing
XVII, 258 p.
Keywords: A topical and authoritative examination of the current crisis in the fishing industry, offering a political analysis of the reasons for the crisis and suggesting ways in which this might be overcome. The contributors include fishery officials and scientists as well as academics. The focus is mainly on the European fishing industry, with issues including political bargaining in the EU, the working of quota arrangements, the status of marine scientific knowledge and the industry's management structures in different countries.